The impact of job security on entrepreneurial activities: The case of Sultanate of Oman - Kahlan Ali Said Al-Maharbi; Essia Ries Ahmed (Journal of Enterprise and Development (JED), 2023)
Purpose — The main goal of this study is to determine the relationship between job security and entrepreneurial activities.Method — This study used the quantitative method and secondary data in this investigation. The questionnaire was collected from 96 entrepreneurs for the sample size, where the collected data is from the Global Entrepreneurship Monitor (GEM) project database in Oman. The Smart-PLS technique’s simple regression method was employed to analyze data.Result — The empirical result found that there is a significant link between job security and entrepreneurial activity. In addition, job security makes the entrepreneur develop long-term strategic plans. In general, the government orientations in Oman 2040 vision support entrepreneurship and support openness, while Oman 2040 vision wants to reduce the contribution of oil revenues and raise the contribution of non-oil revenues.Contribution — This research contributes to the existing literature by improving the understanding of the significance of job security in improving entrepreneurial activity practices for entrepreneurs' projects. Furthermore, the finding provides empirical evidence of the ability of job security to be a valuable instrument for sustainable entrepreneurial activity.